Skrining Fitokimia dan Uji Antioksidan Ekstrak Biji Kopi Sangrai Jenis Arabika (Coffea arabica) Asal Wamena dan Moanemani, Papua - Septiani Mangiwa; Agnes Eri Maryuni (Jurnal Biologi Papua, 2019)
Coffee bean are rich of secondary metabolits that able to inhibit free radical compounds. This antioxidant activity may reduce many diseases correlated with it. The aims of this study were to determined the phytochemical content and antioxidant activity of roasted coffee bean from Wamena and Moenemani regency, Papua. Roasted coffee beans were extracted by maceration for 24 hr with methanol. Harborne standard method was used for the phytochemical analysis  and DPPH assay was used to  determine the antioxidant activity. IC50 was measured by spectrophotometric assay using spectrophotometer Uv-Vis at 517 nm wavelenghth. Result showed that both Arabica roasted coffee beans from Wamena and Moanemany had the capacity to inhibit free radical  at 61,71% and 69,7% with IC50 at  107,97 and 100,91 ppm, respectively . Phytochemical investigation revealed that the bioactive compounds from Moanemani and Wamena coffee beans were similar, which composed of alkaloids, flavonoids, terpenoids, saponins, and tanins. In conclusion, the methanolic extract of roasted Arabica coffee beans from Wamena and Moanemani can be used as the source of natural antioxidant.Keywords: Arabica roasted coffee beans; phytochemical; antioxidant; DPPH method.